2016
DOI: 10.1371/journal.pone.0162624
|View full text |Cite
|
Sign up to set email alerts
|

Towards a DNA Barcode Reference Database for Spiders and Harvestmen of Germany

Abstract: As part of the German Barcode of Life campaign, over 3500 arachnid specimens have been collected and analyzed: ca. 3300 Araneae and 200 Opiliones, belonging to almost 600 species (median: 4 individuals/species). This covers about 60% of the spider fauna and more than 70% of the harvestmen fauna recorded for Germany. The overwhelming majority of species could be readily identified through DNA barcoding: median distances between closest species lay around 9% in spiders and 13% in harvestmen, while in 95% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 87 publications
0
87
1
Order By: Relevance
“…The spider samples were collected from different locations including human houses.The spider species used in the current study was identified as Hasarius adansoni by amplification of 889 bp of ribosaml RNA ( rRNA ) gene large subunit and 705bp in length of the 5’-end of mitochondrial cytochrome c oxidase subunit 1( COI ) gene. The fragments of rRNA and COI were amplified using specific primer sets Sp28SN/Sp28SC (Starrett and Hedin, 2007), and SP-LCO 1490FJJ/SP-HCO2198RJJ (Astrin et al, 2016), respectively. The spider species was confirmed with complete homology of the two fragments with H .…”
Section: Methodsmentioning
confidence: 99%
“…The spider samples were collected from different locations including human houses.The spider species used in the current study was identified as Hasarius adansoni by amplification of 889 bp of ribosaml RNA ( rRNA ) gene large subunit and 705bp in length of the 5’-end of mitochondrial cytochrome c oxidase subunit 1( COI ) gene. The fragments of rRNA and COI were amplified using specific primer sets Sp28SN/Sp28SC (Starrett and Hedin, 2007), and SP-LCO 1490FJJ/SP-HCO2198RJJ (Astrin et al, 2016), respectively. The spider species was confirmed with complete homology of the two fragments with H .…”
Section: Methodsmentioning
confidence: 99%
“…(). DNA extraction, polymerase chain reaction and sequencing followed standard protocols (Astrin et al., ) and are described together with the newly developed specific primers in detail in Data . All data are deposited in BOLD (https://doi.org/10.5883/gcolzfmk) and GenBank (accession numbers –) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence alignment was performed in MEGA X v. 10.0.5 (Kumar, Stecher, Li, Knyaz, & Tamura, 2018) using MUSCLE (Edgar, 2004) with the default settings. The resulting alignment (Appendix S3) was trimmed to length of 653 bp corresponding to Astrin et al (2016). The shortest included sequence was composed of 540 bp.…”
Section: Molecular Datamentioning
confidence: 99%
“…Interestingly, however, data from the German Barcode of Life campaign (GBOL, https://www.bolgermany.de/) revealed that COI sequences of M. pulicaria fall into two distinct clusters with a p‐distance of ca. 6% (Astrin et al, ), further suggesting that the species deserves a thorough taxonomic reconsideration.…”
Section: Introductionmentioning
confidence: 99%